Thematic and prospective analysis of open science studies within Web Of Science - Paz Enrique, Luis Ernesto; Artigas Morales, Wileidys; Hernández Alfonso, Eduardo Alejandro (Revista Cubana de Salud y Trabajo, 2026)
Introduction: Open science has gained increasing relevance in contemporary scientific communication due to its emphasis on transparency, accessibility, and social engagement. The growing adoption of open access policies and collaborative research practices has transformed knowledge production, making it necessary to analyze its thematic evolution, actors, and structural dynamics. Objective: To analyze the scientific production on open science through a bibliometric approach, identifying publication trends, leading contributors, thematic structures, and emerging research lines. Methods: An observational, descriptive, and bibliometric study was conducted. Data were extracted, normalized, and analyzed using RStudio and the Bibliometrix package. Indicators related to publication trends, citations, authorship, countries, collaboration networks, keywords, and thematic evolution were examined. Results: The findings reveal a sustained increase in scientific production, driven mainly by international collaboration and open science policies. The United States, the United Kingdom, Germany, and Spain stand out as the most productive countries. Citizen science, open data, and open access emerged as central themes, while technological applications and responses to global challenges, such as climate change and COVID-19, appear as emerging topics. Thematic mapping shows a dual structure that combines normative, technological and applied-participatory axes, highlighting strong links between transparency, data accessibility, and social engagement. Conclusions: Open science exhibits a growing interdisciplinary and international character. Its development shows strong potential to guide future research agendas, strengthen collaborative networks, and promote methodological innovation and social impact within the scientific ecosystem. .